Heterogeneity of the fibre sequence in subgenus C adenoviruses. Issue 6 (27th May 2004) - Adhikary, A K; Banik, U; Numaga, J; Suzuki, E; Inada, T; Okabe, N
Abstract : Aims: To determine the nucleotide sequences of adenovirus (Ad) types 1 and 6 fibre genes; to clarify the molecular basis of the distinct haemagglutination properties of subgenus C Ads and their phylogenetic relations. Methods: Human Ad1 and Ad6 fibre genes were sequenced from genomic DNA by direct sequencing. Primer selection was based on alignment of the fibre gene of human Ad serotypes Ad2 and Ad5. Fibre based subgenus C specific polymerase chain reaction (PCR) was performed to check for deletions in field isolates of Ad6, as revealed by sequence analysis of the Ad6 prototype. A phylogenetic tree was constructed from the predicted amino acid (AA) sequences of the fibre gene of important Ads. Results: Ad1 and Ad6 comprise 1746 and 1584 nucleotides, encoding 582 and 528 AA, respectively. Ad6 showed deletions in motifs 15–17 (51 AA) of the shaft when compared with Ad1, Ad2, and Ad5. Subgenus C specific PCR with both prototype and field isolates also showed deletions in Ad6. In the shaft and knob, AA homology was 58.82–72.91% and 68.89–74.59%, respectively. The tail was 100% conserved. Phylogenetically, Ad1 and Ad6, including Ad2 and Ad5, formed a subgenus specific cluster, like other serotypes. Conclusions: The fibre gene (including the knob region) of subgenus C Ads is heterogeneous, providing the molecular basis for lack of crossreactivity in the haemagglutination inhibition test. This heterogeneity could be helpful in fibre based genotyping of subgenus C field isolates. Phylogeny might be useful for subgenus specific identification of important field strains.